Optimization of Extraction of Bioactive Compound from Pegagan Leaves Using Ethanol Solvent With Microwave-Assisted Extraction Method (MAE) - Fira Ulvatur Romah; Atiqa Rahmawati; Meta Fitri Rizkiana; Ari Susanti (University of Jember, 2022)
Treatment using natural ingredients in Indonesia is the leading choice, and it is growing in society. This is because treatment with natural ingredients has relatively milder side effects than synthetic treatment. Therefore, further research is needed on natural ingredients that can be used as natural medicines, including pegagan (Centella asiatica (L.)). Several studies have found bioactive compounds in pegagan that can be used in various medical methods. The author wants to know the optimal conditions for extracting pegagan bioactive compounds using the microwave-assisted extraction (MAE) method. This study used the Pegagan leaf size 40 mesh that had been dried. Pegagan leaves were extracted using ethanol as a solvent with microwave power, solvent concentration, and extraction time as variables. Variable power: 150 watts, 300 watts, and 450 watts. Variable solvent concentration 25%, 50%, and 75%. Variable extraction time for 5, 10, and 15 minutes. The results of the study were analyzed using total phenol analysis using the Folin-Ciocalteu method. The research data obtained optimum operating conditions at 75% solvent concentration, 450-watt microwave power, and an extraction time of 10 minutes with a total phenol content of 1251.410225 mg AGE/g sample.